Α‐Linolenic acid‐derived metabolites from gut lactic acid bacteria induce differentiation of anti‐inflammatory M2 macrophages through G protein‐coupled receptor 40. Issue 1 (13th September 2017) - Ohue‐Kitano, Ryuji; Yasuoka, Yumiko; Goto, Tsuyoshi; Kitamura, Nahoko; Park, Si‐Bum; Kishino, Shigenobu; Kimura, Ikuo; Kasubuchi, Mayu; Takahashi, Haruya; Li, Yongjia; Yeh, Yu‐Sheng; Jheng, Huei‐Fen; et al.
Abstract : Among dietary fatty acids with immunologic effects, ω‐3 polyunsaturated fatty acids, such as a‐linolenic acid (ALA), have been considered as factors that contribute to the differentiation of M2‐type macrophages (M2 macrophages). In this study, we examined the effect of ALA and its gut lactic acid bacteria metabolites 13‐hydroxy‐ 9(Z), 15(Z)‐octadecadienoic acid (13‐OH) and 13‐oxo‐9(Z), 15(Z)‐octadecadienoic acid (13‐oxo) on the differentiation of M2 macrophages from bone marrow‐derived cells (BMDCs) and investigated the underlying mechanisms. BMDCs were stimulated with ALA, 13‐OH, or 13‐oxo in the presence of IL‐4 or IL‐13 for 24 h, and significant increases in M2 macrophage markers CD206 and Arginase‐1 (Arg1) were observed. In addition, M2 macrophage phenotypes were less prevalent following cotreatment with GPCR40 antagonists or inhibitors of PLC‐β and MEK under these conditions, suggesting that GPCR40 signaling is involved in the regulation of M2 macrophage differentiation. In further experiments, remarkable M2 macrophage accumulation was observed in the lamina propria of the small intestine of C57BL/6 mice after intragastric treatments with ALA, 13‐OH, or 13‐oxo at 1 g/kg of body weight per day for 3 d. These findings suggest a novel mechanism of M2 macrophage differentiation involving fatty acids from gut lactic acid bacteria and GPCR40 signaling.—Ohue‐Kitano, R., Yasuoka, Y., Goto, T., Kitamura, N., Park, S.‐B., Kishino, S., Kimura, I., Kasubuchi, M., Takahashi, H., Li, Y., Yeh, Y.‐S., Jheng, H.‐F., Iwase, M., Tanaka, M., Masuda, S., Inoue, T., Yamakage, H., Kusakabe, T., Tani, F., Shimatsu, A., Takahashi, N., Ogawa, J., Satoh‐Asahara, N., Kawada, T. α‐Linolenic acid‐derived metabolites from gut lactic acid bacteria induce differentiation of anti‐inflammatory M2 macrophages through G protein‐coupled receptor 40. FASEB J. 32, 304‐318 (2018). www.fasebj.org